Long‐Life Zn Anode Enabled by Low Volume Concentration of a Benign Electrolyte Additive. (25th March 2022) - Shang, Yuan; Kumar, Priyank; Musso, Tiziana; Mittal, Uttam; Du, Qijun; Liang, Xiao; Kundu, Dipan
Abstract: Inexpensive and energy‐dense Zn metal anodes is key to the promise of aqueous Zn‐ion batteries, which are heralded as an exciting battery chemistry for renewable and stationary storage. Yet, Zn deposition instability under demanding cycling conditions leads to rapid dendritic cell failure, and the hydrogen evolution reaction aggravates the issue. Electrolyte additives are a scalable solution to address the problem, but a high volume fraction is typically required for a noticeable effect. Here, a benign alcohol molecule propylene glycol is presented as an electrolyte additive that enables remarkably stable Zn anode cycling of over 1000 h at a practical 2 mA–2 mA h cm −2 at a low volume concentration when the reference cell shorts only after 30 h. The dramatic performance improvement at the low additive concentration is attributed to the effective morphology regulation and inhibition of hydrogen evolution, as revealed by spectroscopic and microscopic investigations. Ab initio molecular dynamics simulations reveal unprecedented atomistic insights behind the concentration‐dependent effectivity of propylene glycol as an electrolyte additive. Excellent full cell cycling with two different positive host materials, even with high loading, highlights the potential for practical development. Abstract : An alcoholic molecule propylene glycol is introduced as a benign electrolyte additive to enable long‐term dendrite‐free cycling of the Zn anode with the aqueous ZnSO4 electrolyte at a much lower volume concentration than the analogous additives. Besides experimental validation of the origin of concentration‐dependent effectivity, ab initio molecular dynamics simulations shed light on the atomistic rationale.